The Notary Authority in the Making of Land Waqf Prediction Deed - Febryan, Rinaldy Bagus; Sulchan, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Before donating the property of the Wakif, the Wakif must make his Waqf pledge first. Then it is poured into writing, carried out in the presence of the Official Making the Waqf Pledge Deed (PPAIW). The Wakif statement will then be stated in a form of Deed, which is called the Waqf Pledge Deed. The provisions of the requirements for a Notary to become PPAIW are explained in the Regulation of the Minister of Religion Number 73 of 2013 concerning Procedures for Waqf of Immovable and Movable Objects Other than Money. This study uses a normative juridical research approach, examining the implementation or implementation of positive legal provisions and factual contracts in each particular legal event. The results of this study are 1) Notary authority in making Waqf Pledge Deed (AIW) has been given by Article 37 PP No. 42 of 2006, but not all Notaries can be appointed as PPAIW. The main requirements for a Notary to become PPAIW must be Muslim, trustworthy and have a certificate of competence in the field of Waqf issued by the Ministry of Religion; 2) The inhibiting factor in the implementation of the Notary in making the Waqf Pledge Deed is that the people of Jepara Regency only know that PPAIW is the Head of the sub-district KUA in the Jepara Regency Legal area, because until now there has been no Notary in Jepara Regency who has obtained certification as PPAIW in relation to making AIW.